Does the opening of high-speed railway improve air quality? Evidence from China. (December 2022) - Zhu, Xinhua; Dai, Chun; Wei, Yigang
Abstract: This study aims to investigate the effects and mechanisms of the opening of HSR on air quality in China. The Difference-in-Difference-in-Differences estimation approaches are used to explore the cases of 271 cities during 2007–2016. Results are presented as follows. (1) The opening of HSR has generally improved the air quality significantly. Compared with cities with no HSR, the PM2.5 concentration in cities with HSR has been lowered by 3.5%; (2) From a dynamic perspective, the pollution inhibition effects of HSR start in the first and second years after the opening; (3) Heterogeneity analysis shows that the air quality of cities with HSR affected by the Ten Clauses by The State Council is significantly improved; (4) Mechanism analysis shows that the opening of HSR has affected the PM2.5 concentration through three ways: the substitution effect on traditional means of transportation, the optimisation of industrial structure and the influence of technological progress. Highlights: Investigate the effects and mechanisms of HSRs on urban land expansion by using multi-stage difference-in-differences (DID) estimation method. Each newly added station will increase the urban land expansion index by 2.4%. Urban land expansion will experience a 4.8% increase when a new HSR route is added. The positive effects of the opening of HSRs have a time lag of five years. Obvious heterogeneity exists between different cities with regard to the HSR effect on urban land expansion.